Economic Evaluation, Land/Water Use, and Sustainable Nature Conservation of 'De Vechtstreek' Wetlands - Ernst J. Bos; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 1998)
Elements of an integrated analysis of a land/water use and nature conservation in De Vechtstreek area are presented. This is a river plane composed of patches of lakes and polders, in the centre of The Netherlands. The attention is focused on the economic dimensions of the research. To this end, an overview is given of available information for a set of main wetland function and use categories. This includes estimates of costs and benefits associated with particular activities. These are used in an illustrative cost-benefit analysis of a change to more nature conservation in De Vechtstreek. The method makes use of the assumption that there are fixed relationships between land/water use area size and values. It is concluded that the nature conservation is a rational economic strategy for discount rates below 13% for a time horizon of 10 years, up to 18% for an infinite time horizon. The approach is aimed to be applied to other scenarios than nature conservation as well, in which case integration with nature science information and models will be pursued, as well as estimation of benefits transfer functions.
Keywords: 330; Naturschutz; Bewertung; Kosten-Nutzen-Analyse; Gewässerschutz; Bodenschutz; Niederlande